Utah Politics and Government : American Democracy among a Unique Electorate - Brown, Adam R. (Book collections on Project MUSE., 2018)
"Utah Politics and Government covers Utah's religious heritage and territorial history, its central political institutions, and its political culture, while situating Utah within the broader American political setting"--